Twin pregnancies: can sonographic measurements and changes in cervical length during pregnancy predict preterm birth?. (3rd May 2022) - Weitzner, Omer; Yagur, Yael; Biron-Shental, Tal; Tzadikevitch-Geffen, Keren; Bookstein, Shiran; Markovitch, Ofer
Abstract: Objective: This study measured cervical length (CL) at 14–16 and 21–24 weeks of gestation and assessed whether the difference between measurements is predictive of preterm birth (PTB) among asymptomatic women with twin gestations. Method: This retrospective, cohort study included patients with two consecutive CL measurements with transvaginal sonography at 14–16 weeks of gestation (CL1) and 21–24 weeks (CL2). PTB was defined as delivery prior to 37 + 0 weeks of gestation. Electronic medical records were reviewed for demographic, medical and delivery data. CL1, CL2 and the change between scans were evaluated and correlated with the prediction of PTB. Results: Among 103 women with twin gestations, 76 (73.7%) delivered at term and 27 (26.3%) had PTB. CL1 and CL2 were not good predictors of PTB ( p  = .32 and p  = .38, respectively). The correlation between CL change and PTB was not significant ( p  = .08). The correlation between CL change and delivery after 38 weeks was not significant ( p  = .3). Baseline characteristics and perinatal outcomes between term and preterm deliveries were similar. Conclusions: The delta between routine cervical length measurements at 14–16 and 21–24 weeks of twin gestations cannot be used as a reliable predictor of PTB.